Characterization and typification of coffee production systems (Coffea arabica L.), Andes municipality (2017)
The Southwestern region of Antioquia has been characterized for being at the forefront of coffee production in Colombia, with a high diversity in production systems. The research was intended to characterize and typify 13 coffee production systems (Coffea arabica L.) in Andes Municipality (Antioquia) under several types of management. The methodology included the qualitative characterization of aspects such as socio-demography, environment, economics, and agriculture, followed by a classification. Statistical multiple-correspondence analyses were conducted and the cluster method was applied. Results on the evaluation of sizes show that concerning the socio-demographic dimension 100% coffee growers own the land, completed primary school, hold a property area between three and four hectares, and have over 20 years of experience in the field; with respect to the environmental dimension, 100% coffee growers have traditional benefits and their coffee is sundried, and between 46% and 69% of them used chemical fertilizers. In relation to the economic aspect, 77% of coffee growers market through unions and experience high production costs with no profit. Finally, concerning the agricultural aspect 100% of coffee growers prepare their soil with minimum farm work and purchase the seeds; 85% of them engage workforce; and 46% of them own low-quality soils and biodiversity. Typification showed that 47% of coffee growers resort to conventional systems (use of chemical products); 38% of them use Transition I systems (Rationalization of Synthetic Supplies); and only 15% of them use Transition II systems (Use of Organic Supplies).